已知信号f(t)的波形如下图所示,则f(t)的表达式为( )[img=337x218]1803c214dd3ccce.png[/img]
A: δ(t-1)+(t+1)u(t)
B: δ(t+1)+tu(t)
C: δ(t+1) +(t-1)u (t)
D: δ(t+1)+(t+1)u(t)
A: δ(t-1)+(t+1)u(t)
B: δ(t+1)+tu(t)
C: δ(t+1) +(t-1)u (t)
D: δ(t+1)+(t+1)u(t)
举一反三
- 已知f(t)的波形如下图所示,则f(t)的表达式为[img=183x135]17869c17a5df3e3.bmp[/img] A: f(t)=(t+1)ε(t)-(t+1)ε(t+1) B: f(t)=tε(t)-(t-1)ε(t-1) C: f(t)=tε(t)-tε(t-1) D: f(t)=(1-t)ε(t)-(1-t)ε(t-1)
- 已知f(t)的波形如下图所示,则f(t)的表达式为 A: f(t)=tε(t)-tε(t-1) B: f(t)=tε(t)-(t-1)ε(t-1) C: f(t)=(1-t)ε(t)-(1-t)ε(t-1) D: f(t)=(t+1)ε(t)-(t+1)ε(t+1)
- 已知信号f(t)的波形如图所示,则f(t)的表达式为() A: (t+1)ε(t) B: δ(t-1)+(t-1)ε(t) C: (t-1)ε(t) D: δ(t+1)+(t+1)ε(t)
- 下列计算正确的是_____。 A: u(t+1)*u(t−1)=tu(t) B: [img=116x24]1803c9ed70c142c.png[/img] C: sin(t)*δ’(t)=−δ(t) D: cos(πt)*δ(t−2)=1
- 下列计算正确的是_____。 未知类型:{'options': ['u(t+1)*u(t−1)=tu(t)', '', 'sin(t)*δ’(t)=−δ(t)', 'cos(πt)*δ(t−2)=1'], 'type': 102}